2003
DOI: 10.1021/bi033012g
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Necrosis Factor-α Converting Enzyme (TACE):  A Unique Metalloproteinase with Highly Defined Substrate Selectivity

Abstract: Pages 9465 and 9466. The sequence shown as the cleavage site of erbB4/HER4 (HGLSLPVENRLYTYDH) in Figure 1 and Table 1 is actually the cleavage site of the heparinbinding epidermal growth factor (HB-EGF). Moreover, reaction products shown in Figure 2 (bottom right panel) correspond also to the cleavage of HB-EGF by TACE, not HER4. Therefore, every reference in Materials and Methods and Results to erbB4/HER4 actually corresponds to HB-EGF. While this inadvertant mislabeling of the HB-EGF substrate as HER4 is unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 0 publications
6
75
0
2
Order By: Relevance
“…In particular, although TACE is considered to be the major physiological TNF sheddase, responsible for 90% of its cleavage in vivo, 3 other cell surface sheddases in the metalloprotease family, such as ADAM-10 and matrix metalloprotease (MMP)-7, have been shown to possess some, albeit small, TNF-cleaving activity. 6,21,22 However, we found that specificity constant (k cat /K m ) for the cleavage of FAM-TAMRA TNF peptide by rADAM-10 was eight-fold lower than that by rTACE, consistent with previous published data by Moss et al 6 Mohan et al 22 reported that the k cat /K m for the cleavage of a similar peptide with a TACE-sensitive TNF sequence was 200-fold lower with rMMP-7 than rTACE. These in vitro experiments using recombinant enzymes suggest that if hydrolysis of the FAM-TAMRA peptide in cell-based assays is metalloprotease-dependent, then the observed enzyme activity should be attributable mainly to TACE, rather than ADAM-10 or MMP-7.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, although TACE is considered to be the major physiological TNF sheddase, responsible for 90% of its cleavage in vivo, 3 other cell surface sheddases in the metalloprotease family, such as ADAM-10 and matrix metalloprotease (MMP)-7, have been shown to possess some, albeit small, TNF-cleaving activity. 6,21,22 However, we found that specificity constant (k cat /K m ) for the cleavage of FAM-TAMRA TNF peptide by rADAM-10 was eight-fold lower than that by rTACE, consistent with previous published data by Moss et al 6 Mohan et al 22 reported that the k cat /K m for the cleavage of a similar peptide with a TACE-sensitive TNF sequence was 200-fold lower with rMMP-7 than rTACE. These in vitro experiments using recombinant enzymes suggest that if hydrolysis of the FAM-TAMRA peptide in cell-based assays is metalloprotease-dependent, then the observed enzyme activity should be attributable mainly to TACE, rather than ADAM-10 or MMP-7.…”
Section: Discussionsupporting
confidence: 90%
“…This may well be initiated by shedding of c-kit ligand. Not only ADAM33 [32] but also ADAM8 [33], ADAM9 [34], ADAM17 [35,36], and ADAM19 [20] are capable of shedding of c-kit ligand, also known as stem cell factor (SCF). SCF plays, apart from its main role as hemopoietic growth factor, a role in recruitment and in maturation of mast cell progenitors [37], sustaining the survival and maintaining phenotypic properties of mast cells in mucosal tissues [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Once the protein has been translated to its precursor form it is inserted in the cell membrane as a pro-TNF 26 kDa form. Membrane-bound TNF may play some role in cell-cell interactions 20 but full activation requires proteases, including TACE and several MMPs, 21 to cleave the protein. Once released as a bioactive trimer it exerts its function by interaction with its membrane receptors TNFRSF1A (TNFRI) and TNFRSF1B (TNFRII).…”
Section: Introductionmentioning
confidence: 99%